Facile and Effective Synthesis of Non-nobel Metal Oxide Composite Heterojunction Catalyst for CO2 Reduction Reaction - Duc Anh, Le; Batur, Jenaidullah; Mudaber, Sebghatullah (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2, 2025)
Increasing CO 2 emmision leads to global warming. Effective and impotent strategies such as photocatalytic CO 2 reduction and utilization was proposed to solve this issue by using sustainable solar energy. We provided a novel, facile, and eco-friendly synthesis strategy to effectively synthesize TiO 2 -organic composite materials to selectively reduce CO 2 to CO. This strategy not only improves TiO 2 photocatalytic activity but also shows potential to apply with alternate metal oxide composite catalyst.